A unique Microfiltration membrane derived from the poly(ethylene-co-methyl acrylate)/Poly(vinylidene fluoride) (EMA/PVDF) biphasic blends and surface modification for antifouling application. (October 2019) - Remanan, Sanjay; Chandra Das, Narayan
Abstract: A new polymeric blend system is developed from the EMA and PVDF by melt-mixing at various blend compositions. Different techniques characterize the prepared blends, and especially, optical microscopy, XRD, and SAXS analyses study the blend crystallization. A microporous structure is prepared by selective solubilization of PVDF from the EMA/PVDF blends can be used as a membrane filter. The membrane prepared at various blend compositions from 90/10 to 60/40 ratio and tested in the cross-flow filtration cell. 70/30 membrane shows high water flux, and porosity is chosen for compaction and antifouling experiments. Membrane surface is modified with a nanocomposite prepared from poly(ethylene imine) and reduced graphene oxide (PEI/rGO) mixture at different concentrations to study the antifouling property during the BSA filtration. 5 wt% filler membrane shows improved flux recovery ratio (FRR) and lowest irreversible flux recovery ratio (IFR) compared to the control membrane. Graphical abstract: Image 1 Highlights: EMA/PVDF blend prepared by melt mixing and characterized by various techniques. Polymer blend crystallinity studied by SAXS and XRD. EMA microporous membrane is developed by selective-etching method. High water flux and less membrane compaction is observed for both 70/30 and 60/40 membrane. High flux recovery ratio and low irreversible flux recovery ratio for higher filler modified 70/30 membrane.